Occlusal assessment in surgically assisted unilateral cleft lip and palate patients - Leanne Matias Portela Leal; Marcus Vinicius Neiva Nunes do Rego; Cosme José Albergaria da Silva Filho; Leopoldino Capelozza Filho; Mauricio de Almeida Cardoso (Dental Press Editora, 2013)
OBJECTIVE: The aim of this study was to assess the magnitude of occlusal changes in individuals with unilateral cleft lip and palate (CLP). The study was conducted on study casts of 25 subjects, 14 men and 11 women aged from 7 to 20 years, without previous orthodontic treatment and with surgical repair carried out at São Marcos Hospital, Teresina, Piauí State, Brazil. METHODS: The casts were assessed by three orthodontists based on the occlusal scores established by Atack et al., whose scores range from 1 to 5, according to the magnitude of transverse and sagittal changes. RESULTS: Intra and inter-observer reproducibility of occlusal scores was satisfactory and statistically significant according to the Spearman Correlation test with significance level set at 5%. With regard to the distribution of occlusal scores, 30.67% of the subjects achieved scores 1 and 2, 22% score 3 and 47.53% achieved scores 4 and 5. CONCLUSIONS: Four was the score most frequently assigned by the observers, disclosing a high degree of transverse and sagittal disorders in the occlusion of patients.